Crystal structure and actuation mechanisms in morphotropic phase boundary Pb(Zn1/3Nb2/3)O3‐Pb(Zr1/2Ti1/2)O3 piezoelectric ceramic. Issue 6 (16th February 2021) - Zhang, Jianbo; Liu, Hui; Sun, Shengdong; Liu, Ye; Zhang, Yueyun; Qi, He; Deng, Shiqing; Chen, Jun
Abstract: Lead‐based Pb(Zn1/3 Nb2/3 )O3 ‐Pb(Zr1/2 Ti1/2 )O3 (PZN‐PZT) piezoelectric ceramics have been intensively studied owing to their excellent performance in multilayer actuators; however, the detailed crystal structure and actuation mechanisms are still not well understood. In this study, in situ electric‐field‐biasing high‐energy synchrotron X‐ray diffraction was employed to monitor the crystal structure evolution and to deconvolute contributions to the electrostrain in the morphotropic phase boundary composition of 0.3PZN–0.7PZT. An electric‐field‐induced reversible phase transition between the coexisting monoclinic and tetragonal phases was identified. The unit cell parameters of the monoclinic phase exhibit significantly greater response to the electric field than those of the tetragonal phase. The effective lattice strain, evaluated through peak profile fitting, and the macroscopic strain measurement were found to be in agreement. The high electrostrain is primarily caused by the electric‐field‐induced phase transition with concurrent intrinsic/extrinsic contributions. This work provides a deeper description of the crystal structure and actuation mechanisms in PZN‐PZT piezoelectric systems.